Dreaming in sleep disorders: a comparative analysis of REM and NREM parasomnias - See, Qi Rui (Nanyang Technological University, 2023)
Parasomnias are abnormal behaviours emanating from or associated with sleep and dreaming. By studying the dream content and observing the isomorphism in these parasomnias, in which dreams are translated into simple/complex behaviours, it provides a valuable window to the underlying cognitive mechanisms during REM and NREM sleep. The aim of this study was to quantify the differences between RBD and NREMP patients in terms of their sleep physiology and dream mentation. This was achieved by exploring their dream content and structure using the Orlinski scale, Hall and Van de Castle analysis and speech graph analysis. RBD patients were found to experience significantly higher dream recall/complexity and displayed fight behaviour in a fight-or-flight response. The novel use of speech graphs on dream reports were also found to be useful in differentiating between RBD and NREMP patients, in which RBD patients showed a pattern of linearity while NREMP patients exhibited convolution. This uncovers the potential of using speech graph analysis as a cost- efficient, fast and complementary tool in the differential diagnosis of these two parasomnias and in tracking disease progression. This allows for early intervention to introduce neuroprotective agents that may mitigate the progression of Parkinson’s and other neurodegenerative diseases.